2019
DOI: 10.1186/s12967-019-1844-0
|View full text |Cite
|
Sign up to set email alerts
|

Altered PGE2-EP2 is associated with an excessive immune response in HBV-related acute-on-chronic liver failure

Abstract: Background and aimsProstaglandin E receptor 2 (EP2) is an immune modulatory molecule that regulates the balance of immunity. Here we investigated the role of EP2 in immune dysregulation in patients with acute-on-chronic liver failure (ACLF).MethodsPlasma Progstaglandin E2 (PGE2) levels and EP2 expression on immune cells were determined in blood samples collected from patients with chronic hepatitis B related ACLF(HB-ACLF), patients with chronic hepatitis B (CHB), acute decompensated cirrhosis without ACLF (AD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“… 69 Stimulating DRD1 negatively regulates the activation of NLRP3 inflammatory bodies through cAMP, thereby regulating the occurrence of inflammation. 70 In addition, DR exists in a variety of immune cells, such as regulatory T cells (Tregs), effector T cells (Teffs), and NK cells. DRD1 involves the inhibition of CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“… 69 Stimulating DRD1 negatively regulates the activation of NLRP3 inflammatory bodies through cAMP, thereby regulating the occurrence of inflammation. 70 In addition, DR exists in a variety of immune cells, such as regulatory T cells (Tregs), effector T cells (Teffs), and NK cells. DRD1 involves the inhibition of CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive production of inflammatory mediators including cytokines, chemokines, growth factors, bioactive lipid mediators, and expression of chemokine receptors by different immune cells induce systemic inflammation, immune-mediated tissue damage, and subsequently liver failure (14)(15)(16)(17)(18)(19). Activated immune cells release other mediators such as proteases, reactive oxygen species (ROS), prostaglandins, and leukotrienes that further aggravate tissue damage (16,20).…”
Section: Pathophysiological Mechanisms In Aclf Systemic Inflammationmentioning
confidence: 99%
“…Currently, oxidative stress is believed to play an important role in liver failure [ 4 ]. During ACLF, injured/dead hepatocytes significantly increase oxidative stress, which leads to additional hepatocyte loss and inhibits regeneration, resulting in a vicious cycle [ 5 , 6 ]. Recent studies have shown that scoring systems for assessing severity and disease outcomes of ACLF have been developed [ 7 ].…”
Section: Introductionmentioning
confidence: 99%